Heat-induced gel formation by whey protein isolate-Lycium barbarum polysaccharides at varying pHs. (June 2021) - He, Zhendong; Ma, Tianyi; Zhang, Weiwei; Su, Erzheng; Cao, Fuliang; Huang, Meigui; Wang, Yaosong
Abstract: Effects of different levels (0, 0.1, 0.5, and 1% w/v) of Lycium barbarum polysaccharides (LBP) were investigated on the gel properties of heat-induced whey protein gels forming at varying pHs (3.0, 5.2 and 7.0). The textural, rheological, hydration properties and microstructure of gels were evaluated. Results exhibited that the composite gel containing 0.1% (w/v) LBP showed the greatest functional valorization, whereas higher concentrations of LBP (1% w/v) yielded hydrogels with higher porosity, which was confirmed by scanning electron microscopy. Moreover, whey protein formed white particulate gels and transparent fibrillar gels at pH values near to and far from the isoelectric point, respectively. As for hydration properties, no difference in water holding capacity and swelling property was observed at all pHs. This study simulated the conditions used in practical production, aiming to provide a theoretical basis for the application of LBP on composite gels and develop tunable gel-type food to satisfy different consumer preferences. Graphical abstract: Image 1 Highlights: Whey protein isolate- Lycium barbarum polysaccharide (WPI-LBP) gel was fabricated by heat-induced gelation. LBP exhibited pH-dependent effects on gelling properties of WPI-LBP gels. pH dominated WPI-LBP gel microstructure and gelling properties thereof. WPI-LBP gel exhibited the variation in the functional properties.